Interplanetary Shocks, Magnetopause Boundary Layers and Dayside Auroras: The Importance of a Very Small Magnetospheric Region - Tsurutani, B. T.; Zhou, X.Y.; Vasyliunas, V.M.; Haerendel, G.; Arballo, J. K.; Lakhina, G. S. (My University, 2001)
Dayside near-polar auroral brightenings occur when interplanetary shocks impinge upon the Earth's magnetosphere. The aurora first brightens near local noon and then propagates toward dawn and dusk along the auroral oval. The propagation speed of this wave of auroral light is âˆ¼10 km s-1 in the ionosphere. This speed is comparable to the solar wind speed along the outer magnetosphere. The fundamental shock-magnetospheric interaction occurs at the magnetopause and its boundary layer. Several physical mechanisms transferring energy from the solar wind directly to the magnetosphere and from the magnetosphere to the ionosphere are reviewed. The same physical processes can occur at other solar system magnetospheres. We use the Haerendel (1994) formulation to estimate the acceleration of energetic electrons to 50 keV in the Jovian magnetosphere/ionosphere. Auroral brightenings by shocks could be used as technique to discover planets in other stellar systems.
Keywords: Aurora; Interplanetary shocks; Magnetopause; Magnetospheric Region; Boundary layer